A dangerous parting: the beheading of John the Baptist in early Christian memory - Shedd, Nathan L. (Baylor University Press, 2021)
"Traces early Christian interpretations of the story of John the Baptist's death by means of memory theory and reception theory, arguing that early Christians used John's beheading to justify hostility toward Jews"